Piperacillin/tazobactam-resistant, cephalosporin-susceptible Escherichia coli bloodstream infections are driven by multiple acquisition of resistance across diverse sequence types - Edwards, T; Heinz, E; van Aartsen, J; Howard, A; Roberts, P; Corless, C; Fraser, AJ; Williams, CT; Bulgasim, I; Cuevas, LE; Parry, CM; Roberts, AP; et al. (Microbiology Society, 2022)
Resistance to piperacillin/tazobactam (TZP) in Escherichia coli has predominantly been associated with mechanisms that confer resistance to third-generation cephalosporins. Recent reports have identified E. coli strains with phenotypic resistance to piperacillin/tazobactam but susceptibility to third-generation cephalosporins (TZP-R/3GC-S). In this study we sought to determine the genetic diversity of this phenotype in E. coli (n=58) isolated between 2014–2017 at a single tertiary hospital in Liverpool, UK, as well as the associated resistance mechanisms. We compare our findings to a UK-wide collection of invasive E. coli isolates (n=1509) with publicly available phenotypic and genotypic data. These data sets included the TZP-R/3GC-S phenotype (n=68), and piperacillin/tazobactam and third-generation cephalosporin-susceptible (TZP-S/3GC-S, n=1271) phenotypes. The TZP-R/3GC-S phenotype was displayed in a broad range of sequence types, which was mirrored in the same phenotype from the UK-wide collection, and the overall diversity of invasive E. coli isolates. The TZP-R/3GC-S isolates contained a diverse range of plasmids, indicating multiple acquisition events of TZP resistance mechanisms rather than clonal expansion of a particular plasmid or sequence type. The putative resistance mechanisms were equally diverse, including hyperproduction of TEM-1, either via strong promoters or gene amplification, carriage of inhibitor-resistant β-lactamases, and an S133G blaCTX-M-15 mutation detected for the first time in clinical isolates. Several of these mechanisms were present at a lower abundance in the TZP-S/3GC-S isolates from the UK-wide collection, but without the associated phenotypic resistance to TZP. Eleven (19%) of the isolates had no putative mechanism identified from the genomic data. Our findings highlight the complexity of this cryptic phenotype and the need for continued phenotypic monitoring, as well as further investigation to improve detection and prediction of the TZP-R/3GC-S phenotype from genomic data.